Neo-Rural Hmong in French Guiana. - Géraud, Marie-Odile (Hmong Studies Journal, 2019)
The Hmong have been living in French Guiana since 1977. They are mainly market gardeners and live in two main villages, which are mostly mono-ethnic. At the end of the 1990s, a new Hmong settlement, Corossony, was founded by Hmong from mainland France, neo-rural and neoagriculturalists, driven by a more individualistic lifestyle and aspiring to work towards ideals of freedom, a return to a more authentically Hmong existence and social success. This study examines the characteristics of these neo-residents who stand apart from other Hmong in French Guiana, living in a way they perceive to be at variance with their previous lives in France. Their situation must be analyzed less as a new relationship to the rural world and to agriculture or a reappropriation of a past way of life than as a counter-model to their integration in mainland France.